Rating the Rating Agencies : Anticipating Currency Crises or Debt Crises? - Sy, Amadou (IMF Working Papers; Working Paper ;, 2003)
In contrast to the early-warning system literature, we find that currency and debt crises are not closely linked in emerging markets. We find that after 1994, credit ratings predict debt crises but fail to anticipate currency crises. When debt crises are defined as sovereign distress-when spreads are higher than 1,000 basis points-we find that countries experience reduced capital market access and high interest rates on their external debt for typically more than two quarters. We also find that lagged ratings and ratings changes, including negative outlooks and credit watches, anticipate such debt crises.